The sea of monsters - Riordan, Rick. (New York Scholastic, 2006)
Demi-god Percy Jackson and his friends must journey into the Sea of Monsters to save their camp. But first Percy will discover a secret that makes him wonder whether being claimed as Poseidon's son is an honor or a cruel joke.
Keywords: Poseidon -- (Greek deity) -- Fiction; Hades -- (Greek deity) -- Fiction; Zeus -- (Greek deity) -- Fiction; Mythology, Greek -- Juvenile fiction; Mythology, Greek -- Fiction; Camps -- Fiction; Friendship -- Fiction; Fathers and sons -- Fiction